Digital Economy and Financial Empowerment: The Mediating Role of Infrastructure, Innovation, and Competitive Advantage - Erna Susilawaty Sebayang (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
MSMEs are a vital pillar of Indonesia’s economy, especially as digital transformation becomes increasingly important for strengthening competitiveness. This study examines the influence of financial empowerment and the digital economy on the performance of micro, small, and medium enterprises in Indonesia, with digital infrastructure, digital financial technology innovation, and competitive advantage as mediating variables. The research addresses how access to finance and digital transformation shape business sustainability in an increasingly competitive environment. Using a quantitative approach with Structural Equation Modeling (SEM-PLS), data were collected from 100 MSMEs through questionnaires, documentation, and observation. The analysis demonstrates that financial empowerment and the digital economy directly affect MSME performance and indirectly through the mediating roles of infrastructure, innovation, and competitiveness. Digital payments, cloud-based financial systems, and fintech lending improve efficiency, transparency, and market expansion, while competitive advantage strengthens MSMEs’ ability to adapt and differentiate in the digital era. The findings highlight that MSMEs leveraging financial access and digital technologies are better positioned to achieve sustainable growth and competitiveness, contributing significantly to Indonesia’s economic development.